Analisa Penyajian Laporan Keuangan Berbasis ERP (SAP) dengan Metode EUCS Di PT. Central Proteina Prima - Mentari, Galih; Yulfajar, Amrina (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2022)
The purpose of this study is to see which SAP is used to provide reports to meet financial reporting requirements, as well as how the EUCS model is used to deliver financial reports. The research approach in this case study is qualitative. Data collection was carried out at PT. Central Proteina Prima through interviews, observations, and documentation. Based on this research, the results of using SAP are considered to meet the report quality requirements.cial reports in accordance with the Indonesian Financial Accounting Standards (SAK), which include the Financial Accounting Standards of the Indonesian Institute of Accountants (DSAK Statement) of the Financial Accounting Standards (PSAK) and the Interpretation of Financial Accounting Standards (ISAK), as well as the Regulations and DSAK Guidelines.